If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 2(4 + -2y) 5y = (4 * 2 + -2y * 2) 5y = (8 + -4y) Solving 5y = 8 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 5y + 4y = 8 + -4y + 4y Combine like terms: 5y + 4y = 9y 9y = 8 + -4y + 4y Combine like terms: -4y + 4y = 0 9y = 8 + 0 9y = 8 Divide each side by '9'. y = 0.8888888889 Simplifying y = 0.8888888889
| 5x+7-4x=8 | | 3m-9+-1=24 | | 2x^2-9=x^2 | | 7=-2(3y-5) | | 6(6x-7)=-86 | | 12x^2-42x+8=0 | | m+3+1=7 | | U^2+5uv+6v^2=0 | | 2x/3+x/2=7 | | 5x^2+3=0 | | 2*(x+5)=3*(2x-7)+15 | | 0.26(2.39x-4.91)=10.64 | | 8x+5+7-2x=q | | 4--4y+3y=1 | | (2x+8)(x)=2170 | | X^3-9x^2+22x-14=0 | | 31-2h/(-7)=-9 | | x+3=2x-9 | | (180-x)-(90-x)=90 | | 3(x-5)+1=34 | | 4A+10= | | -8=y-1/0-(-2) | | 3(y+8)=5y+4 | | -x+7=0 | | 324h^10-361w^2=0 | | -(-5-6n)=4(5n+3) | | 5(x+2)=3x | | 7y=1 | | 2(7x+8)=-5 | | 4-7y=1 | | 13-7x=8x+21 | | -49+10x=14+7x |